Characteristic subgroups of the Jonquere group over a field of characteristic zero - Ivanenko, N. L. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The lattice of characteristic subgroups of the Jonquere group over a field of characteristic zero is described.